Salmonella Contamination of Seafood in Landing Centers and Retail Markets of Mumbai, India. (26th March 2020) - Prabhakar, Parmanand; Lekshmi, Manjusha; Ammini, Parvathi; Nayak, Binaya Bhusan; Kumar, Sanath
Abstract: Background: Seafood contamination with Salmonella enterica is not only a public health concern, but can also lead to economic losses due to import rejections. Continuous monitoring of seafood for Salmonella is necessary for risk assessment and to establish suitable control measures. Objective: The objective of this study was to determine the extent of Salmonella contamination of seafood in fish landing centers and retails markets. Methods: In this study, we analyzed seafood samples from three fish landing centers and seven retail markets of Mumbai, India for S. enterica contamination. Salmonella was isolated using multiple selective enrichment broths and selective agars, and identified by conventional biochemical tests followed by polymerase chain reaction (PCR). Results: Of 82 samples of seafood, comprising both finfish and shellfish, Salmonella was detected in 17 (20.7%) finfish samples. None of the shellfish samples (shrimps, clams, and cephalopods) were found to be contaminated with Salmonella . Samples from both landing centers and fish markets, as well as from pelagic and demersal sources, harbored Salmonella . Source-wise analysis showed that 11 of 57 (19.3%) samples from retail fish markets and 6 of 25 (24%) samples from fish landing centers were contaminated with Salmonella . Conclusions: The study emphasizes the need to implement measures to prevent anthropogenic contamination of coastal waters and improve the hygiene of retail fish markets in Mumbai. Highlights: Seafood from landing centers and retail markets, as well as from pelagic and demersalhabitats were similarly contaminated with Salmonella. Fish species widely consumed in the region of this study were found highly contaminated with Salmonella.